2014
DOI: 10.1002/jssc.201301139
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of various techniques for the extraction and determination of antioxidants in plants

Abstract: The following extraction techniques have been used for extracting antioxidants (apigenin, coumarin, esculetin, umbelliferone, bergapten, quercetin, rutin, scopoletin and xanthotoxin) from plant material: supercritical fluid extraction, pressurized liquid extraction, extraction by means of Soxhlet apparatus, ultrasonic extraction in ultrasonic bath, and by means of ultrasonic probe. The analytical method based on HPLC-UV detection for the determination of selected antioxidants was developed. For all extracts th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 36 publications
0
18
0
Order By: Relevance
“…The most relevant are supercritical carbon dioxide extraction, liquid CO 2 extraction, UAE, MAE and HAE [38][39][40]. There are few works that compare the conventional and alternative extraction techniques [10,17,35].…”
Section: Comparison With Other Studies Involving the Extraction Of Romentioning
confidence: 99%
“…The most relevant are supercritical carbon dioxide extraction, liquid CO 2 extraction, UAE, MAE and HAE [38][39][40]. There are few works that compare the conventional and alternative extraction techniques [10,17,35].…”
Section: Comparison With Other Studies Involving the Extraction Of Romentioning
confidence: 99%
“…These molecules exhibit various biological activities such as antibacterial (Schinkovitz et al, 2003; Stavri et al, 2003; Céspedes et al, 2006), antioxidant (Bajerova et al, 2014), anti-inflammatory (Witaicenis et al, 2013), rodenticidal (Lotfi et al, 1996), termiticidal (Adfa et al, 2010, 2011), and other activities (Stahmann et al, 1941; Murray, 1989; Runkel et al, 1996; Song et al, 2014). In addition, the role(s) of coumarins in plants have also been reported.…”
Section: Introductionmentioning
confidence: 99%
“…The comparison between USAE, and different extraction method developed by other authors, showed the superiority of ultrasound assisted extraction for extracting phenolic compounds for example from Phlomidoschema parviflorum L. leaves (Majd et al, 2014), Thymus vulgaris L. herb, Verbena officinalis L. flovers (Bajerová et al, 2014), Vitis vinifera L. seeds (Da Porto et al, 2013), Ceratonia siliqua (Roseiro et al, 2013) and Betula alleghaniensis (Diouf et al, 2009).…”
Section: Resultsmentioning
confidence: 97%